Knowledge management systems: structural model of its success determinants in Latin America higher education institutions (Journal of Business, Universidad del Pacífico (Lima, Peru), 2021)
This study proposes a structural model of the causal relationships that organizational, strategic, technological, and implementation factors have with knowledge management (KM) processes, as well as those between KM processes and the implementation factors for knowledge management systems (KMSs) at higher education institutions (HEIs) in Latin America. The exogenous variables are: culture of sharing, leadership, KM approach, knowledge map, information management strategy, and ICT. In turn, the endogenous variables are: KM processes, system quality, service quality, KMS use, and user satisfaction. A causal, explanatory, cross-sectional, and ex post facto multivariate study was carried out, using a hypothetical–deductive approach. The sample consisted of 374 individuals (academics, administrators, and researchers), belonging to 193 HEIs across 15 Latin American countries. The resulting model presents a partial fit to the data, confirming the explanatory relationships between 12 of the variables. Based on the results obtained from calculation of the direct and indirect effects observed for each of the endogenous variables of the model, the following goodness of fit indices were calculated: absolute (χ2 = 48.908, P-value= .059, PCMIN= 1.397, RMSEA= .075, FMIN= .689) and incremental (GFI= .894, IFI= .790). It is concluded that leadership, KM approach, knowledge map, and ICT positively influence KM processes; KM processes have a causal relationship with system quality and service quality; and system quality and service quality have an influence on KMS use and user satisfaction.
Keywords: Success factors; knowledge management systems; higher education institutions; structural equation model